Contingent Faculty Composition and Utilization: Perspectives From Independent Colleges and Universities. Issue 176 (25th March 2018) - Morphew, Christopher; Ward, Kelly; Wolf‐Wendel, Lisa
Abstract: This chapter presents a study that explores how faculty composition at independent colleges and universities in the United States has shifted from minimal representation of contingent faculty members in the past to a greater representation presently and the disproportionate expectations and roles placed on these faculty members. Based on the findings, the chapter offers recommendations on how to integrate contingent faculty appropriately to align with institutional missions.